2023
DOI: 10.3390/jcm12031077
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with Arterial Stiffness in Chronic Kidney Disease

Abstract: Background: Arterial stiffness influences the prognosis of patients with end-stage kidney disease; however, the factors that promote arterial stiffness in chronic kidney disease (CKD) patients remain unknown. We aimed to explore the clinical factors associated with arterial stiffness in CKD. Methods: Between September 2017 and September 2022, all CKD patients treated at the Department of Nephrology, General Hospital of the Chinese People’s Liberation Army, excluding dialysis patients, were screened and their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Studies focusing on the association between CKD-MBD markers and AS have shown conflicting results. In a cross-sectional study, serum calcium and phosphorus concentrations were not an independent predictor of AS among CKD patients [44]. Another small study showed that, in patients undergoing peritoneal dialysis, aortic PWV were not correlated with serum calcium, phosphorus, or iPTH levels [45].…”
Section: Discussionmentioning
confidence: 93%
“…Studies focusing on the association between CKD-MBD markers and AS have shown conflicting results. In a cross-sectional study, serum calcium and phosphorus concentrations were not an independent predictor of AS among CKD patients [44]. Another small study showed that, in patients undergoing peritoneal dialysis, aortic PWV were not correlated with serum calcium, phosphorus, or iPTH levels [45].…”
Section: Discussionmentioning
confidence: 93%
“…AS is characterized by chronic structural modifications in the arterial wall expressed by elastin fragmentation and media calcification, but molecular changes in the intimal layer may also occur through the atherosclerotic inflammatory process [12,13].…”
Section: Introductionmentioning
confidence: 99%